1999
DOI: 10.1038/11375
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antigen-specific immunosuppression by CD95L cDNA-transfected 'killer' dendritic cells

Abstract: Dendritic cells (DCs) are special subsets of antigen-presenting cells characterized by their highly potent capacity to activate immunologically naive T cells. Here we report that DCs that are transfected with CD95 ligand (CD95L) cDNA, called 'killer' DCs, deliver death signals, instead of activation signals, to T cells after antigen-specific interaction. Injection of antigen-pulsed killer DCs into mice before sensitization induced antigen-specific immunosuppression. When administered after sensitization, kille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 46 publications
7
149
2
Order By: Relevance
“…In murine systems antigen-specific T cell deletion and tolerance induction in vitro and in vivo was achieved by CD95L-transfected APC. 14,15 Also in the human system mature but not immature human DC retrovirally transduced with murine CD95L induced apoptosis induction in CD95-expressing T cells in vitro. 25 However, to our knowledge, efficient alloantigen-specific depletion by APC expressing m-CD95L without impairment of immunity towards environmental antigens is shown here for the first time in the human system.…”
Section: Cd95l Expressed On T Cells Mediates a Dual Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…In murine systems antigen-specific T cell deletion and tolerance induction in vitro and in vivo was achieved by CD95L-transfected APC. 14,15 Also in the human system mature but not immature human DC retrovirally transduced with murine CD95L induced apoptosis induction in CD95-expressing T cells in vitro. 25 However, to our knowledge, efficient alloantigen-specific depletion by APC expressing m-CD95L without impairment of immunity towards environmental antigens is shown here for the first time in the human system.…”
Section: Cd95l Expressed On T Cells Mediates a Dual Functionmentioning
confidence: 98%
“…13 In mice antigen-specific elimination of activated T cells by engagement of CD95L on APC and CD95 on the activated T cells has been demonstrated in several models. 14,15 This approach benefits from the high specificity since only T cells responding to the antigen expressed on the APC are deleted by CD95/CD95L interaction while the remaining T cells are still responsive to unrelated antigens. However, successful elimination of antigen-specific T cells via the CD95 system depends on the CD95-sensitivity of T cells.…”
mentioning
confidence: 99%
“…However, all these studies were performed using murine DC, B cells, macrophages, or cell lines as APC (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)39). Therefore, for future clinical application, it had to be determined whether human DC can be efficiently transduced with FasL and whether these cells would be capable of eliminating Fas ϩ target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, experiments to generate FasL-expressing APC from primary human cells are still lacking. Because several studies demonstrated that FasL is highly conserved within different species and that murine FasL induces apoptosis in human Fas ϩ cells (18), we investigated in the present study whether primary human monocytederived immature DC (iDC) and mature DC (mDC) could be transduced with murine FasL using an inducible Cre/Loxp adenovirusbased gene transfer system to generate killer APC.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Both the XS106 LC line and NF46 fibroblasts were established from the epidermis of newborn A/J mice and maintained in vitro, as described previously (12)(13)(14).…”
Section: Animals and Cell Linesmentioning
confidence: 99%